2007
DOI: 10.2341/06-166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of New Formulas of Bleaching Gel and Fluoride Application on Enamel Microhardness: An In Vitro Study

Abstract: ©Operative Dentistry, 2007, 32-6, 589-594 JB da Costa • RF Mazur Clinical RelevanceThe results of this study suggest that tooth bleaching may lead to a reduction in enamel microhardness. Nonetheless, the application of a high concentration fluoride post-bleaching treatment may increase enamel microhardness and may restore enamel hardness to a level similar to non-bleached enamel, if the bleaching formula contains fluoride, potassium or ACP. SUMMARYThis in vitro study evaluated the new formulas of bleaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 23 publications
2
47
1
5
Order By: Relevance
“…[21][22][23][24] However, some studies have reported significant increases in enamel surface roughness subsequent to the use of bleaching agents. 8,9 Some of the complications of applying bleaching agents in tooth hard tissues are changes in tooth chemical structure, demineralization and decreases in the mineral content including calcium and phosphate, 14,25,26 decreases in the fluoride content of enamel, 11 and changes in the micromorphology of enamel. 9,27,28 However, other studies have reported different results with no statistically significant differences in tooth hard tissue characteristics, including enamel and dentin surface roughness, after bleaching with 10% and 15% carbamide peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24] However, some studies have reported significant increases in enamel surface roughness subsequent to the use of bleaching agents. 8,9 Some of the complications of applying bleaching agents in tooth hard tissues are changes in tooth chemical structure, demineralization and decreases in the mineral content including calcium and phosphate, 14,25,26 decreases in the fluoride content of enamel, 11 and changes in the micromorphology of enamel. 9,27,28 However, other studies have reported different results with no statistically significant differences in tooth hard tissue characteristics, including enamel and dentin surface roughness, after bleaching with 10% and 15% carbamide peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the other hand, using a fluoride varnish or mouthwash after exposing the teeth to carbamide peroxide can remineralize the enamel. [11][12][13] Because use of saliva or artificial saliva in laboratory studies can also have a role in the remineralization of teeth, 2,7,14 the present study attempted to evaluate changes in enamel surface roughness subsequent to bleaching and brushing at three time intervals and storing the specimens in artificial saliva during the study period. The null hypothesis was that enamel surface roughness is not influenced by when toothbrushing is initiated after bleaching (immediately, at one hour, and at two hours after bleaching).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 On the other hand, saliva or other remineralizing agents can create an environment to help remineralize the teeth following bleaching. [7][8][9][10] Enamel microhardness is a property that can be influenced by a combination of the above-mentioned factors.…”
Section: Introductionmentioning
confidence: 99%
“…Da Costa et coll. (2007) ont constaté que l'émail éclairci avec le peroxyde de carbamide à 10 %, associé au nitrate de potassium à 3 % et au fluor à 0,11 %, a une micro-dureté similaire à celle de l'émail non éclairci [42]. Cependant, Tschoppe et coll.…”
Section: La Fluorationunclassified